2014
DOI: 10.2109/jcersj2.122.714
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and pore characteristics of an alumina coating on a diatomite-kaolin composite support layer

Abstract: Recently porous ceramic membranes have received great interest due to their outstanding thermal and chemical stabilities. In this paper, we investigated whether we could prepare an alumina coating to be deposited over a diatomite-kaolin composite support layer to reliably tailor the permeability by controlling the heat-treatment temperature of the alumina coating. The pore characteristics of an alumina coating on a diatomite-kaolin composite support layer were studied by scanning electron microscopy, mercury p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…(4) We determined the air permeability of the diatomite-kaolin composite-coated diatomite-kaolin composite support layer [17]. (5) the air permeability of an alumina-coated diatomitekaolin composite support layer [15,16,18], along with (6) the water permeability (using pure water) and rejection rate (using ISO 12103-1 A3 test dust) of a diatomite-kaolin composite support layer [13]. Finally, and most notably, (7) we evaluated the water permeability (using pure water) and the reliability of the aluminacoated diatomite-kaolin composite support layer were determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) We determined the air permeability of the diatomite-kaolin composite-coated diatomite-kaolin composite support layer [17]. (5) the air permeability of an alumina-coated diatomitekaolin composite support layer [15,16,18], along with (6) the water permeability (using pure water) and rejection rate (using ISO 12103-1 A3 test dust) of a diatomite-kaolin composite support layer [13]. Finally, and most notably, (7) we evaluated the water permeability (using pure water) and the reliability of the aluminacoated diatomite-kaolin composite support layer were determined.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical strength of a diatomite support layer is not acceptable for a free-standing membrane, therefore, we introduced kaolin to tailor the pore characteristics of the diatomite support layer. Previously, we reported possible approaches for fabrication of a diatomite-based support layer that allowed fine-tuning of the pore characteristics [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches are as follows: (a) the air permeability of the diatomite support layer was enhanced beyond what was previously achieved by controlling the sintering temperature, 13)15) and (b) the largest pore size of the diatomite support layer was reduced through the formation of a diatomite-kaolin composite support layer, 16) through the formation of a diatomite-kaolin composite coating layer, 17) or through the deposition of an alumina coating layer. 18), 19) In previous reports, we measured only the air permeability of diatomite-based support layers to compare our results with the air permeability and/or water permeability of typical ceramic microfiltration membranes reported in the literature. However, at low flow rates, the air permeability of the specimens may be higher than the water permeability of the same specimens, because gas does not adhere to the pore walls the way liquid does and because the slippage of gases along the pore walls causes an apparent dependence of the permeability on the pressure (this is known as the Klinkenberg effect).…”
Section: Introductionmentioning
confidence: 88%
“…Detailed descriptions and basic properties of diatomite have been comprehensively explained in previous reports [18][19][20][21][22][23][24][25][26][27][28][29][30]. Recently, the authors reported several types of porous diatomite such as (1) uniaxially-pressed diatomite-based support layers for microfiltration [18][19][20][21][22][23][24][25][26][27], (2) extruded diatomite-based support layers for microfiltration [28,29], and (3) particle-stabilized diatomite foam with a bimodal pore structure [30]. However, to the best of author's knowledge, there are no studies on the preparation and characterizations of reticulated porous diatomite-kaolin composite.…”
Section: Introductionmentioning
confidence: 99%